2004
DOI: 10.1021/cm0350535
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Stability of Electroluminescent Phenylenevinylene Polymers by Encapsulation in Nanoporous Inorganic Materials

Abstract: Conjugated polyphenylenevinylene oligomer (PPV) encapsulated inside basic zeolites X and Y has been prepared starting from the p-phenylenedimethylene-1,1′-bis(tetrahydrothiophen-1-ium) monomer introduced through ion exchange followed by heating the intermediate poly[1-(S-tetrahydrothiophenium)-p-phenylenethylene] oligomer at 220 °C under vacuum for 24 h. PPV loading ranged between 1.8 and 5 wt %, the sulfur content of the solid being lower than 0.03 wt %, corresponding to 1 S atom every 400 carbons. The organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 32 publications
3
42
0
2
Order By: Relevance
“…The geometrical restrictions imposed by the inorganic host could result in better-organized polymer chains that would facilitate charge injection and transfer between the conducting units. Several research groups have reported the formation of composites of PPV and inorganic two-dimensional insulators [4][5][6][7]; however, intercalates of PPV between the layers of transparent semiconducting divalent metal thiohypophosphates (M II PS 3 or M II 2 P 2 S 6 ) and their luminescent properties have not been explored. In this paper, we report the synthesis and characterization of luminescent organic-inorganic composites containing PPV-intercalated MnPS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The geometrical restrictions imposed by the inorganic host could result in better-organized polymer chains that would facilitate charge injection and transfer between the conducting units. Several research groups have reported the formation of composites of PPV and inorganic two-dimensional insulators [4][5][6][7]; however, intercalates of PPV between the layers of transparent semiconducting divalent metal thiohypophosphates (M II PS 3 or M II 2 P 2 S 6 ) and their luminescent properties have not been explored. In this paper, we report the synthesis and characterization of luminescent organic-inorganic composites containing PPV-intercalated MnPS 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the gradual oxidation of C=C bonds in the polymer results in its degradation, reducing its utility in polymer light-emitting diodes. This oxidation process was markedly retarded within the zeolite [139].…”
Section: Stabilization Of Reactive Intermediatesmentioning
confidence: 96%
“…[86,94] Konjugierte Polymere in Zeolithen sind oft überaus beständig: [22] So kann Polyacetylen in Faujasit unbegrenzt an der Luft gelagert werden, [23] und PPV bleibt im gleichen Zeolith bei der Laserphotolyse unter einer Sauerstoffatmosphäre unverändert. [24] Die TGA-Daten einiger dendronisierter konjugierter Polymere sprechen dafür, dass eine Dendronisierung die thermische Beständigkeit erhöht. So zersetzt sich PPV4(G-1) (Abschnitt 4.4, Schema 14) bei 362 8C, also 34 K oberhalb des vergleichbaren Polymers PPV(G-0), [162] und das Polyfluoren PF5 (Abschnitt 4.3) ist thermisch außerordentlich stabil (Zersetzung bei 570 8C).…”
Section: Beständigkeit Und Chemische Reaktivität Eingeschlossener P-sunclassified
“…lvaro et al beobachteten dennoch eine schwache Elektrolumineszenz für eine LED mit einem 50 mm dünnen Film aus zeolithumschlossenem PPV in Polyacrylamid zwischen einer Indiumzinnoxid-und einer Aluminiumelektrode. [24] Eine effiziente Elektrolumineszenz wurde für Polymer-Ton-und Polymer-MetallchalkogenidNanokomposite ermittelt. [191,192] Diese Nanokomposite ähneln zeolithumhüllten Polymeren, bis auf die Tatsache, dass die Polymerketten in zweidimensionale Zwischenräume eingeschlossen sind und nicht in eindimensionale Kanäle.…”
Section: Elektrolumineszenzunclassified